2012
DOI: 10.1080/10494820.2010.500084
|View full text |Cite
|
Sign up to set email alerts
|

Explaining students' appraisal of lectures and student-activating teaching: perceived context and student characteristics

Abstract: During lectures, some students are continuously focused and attentive, whereas others tend to be bored, jittery, or inattentive. The same might happen when students are given student-activating assignments. Some students simply love one type of instruction, whereas others tend to resent it. Moreover, it is not the context itself, but the context as it is perceived by the student that affects learning. This study sets out to discover how students view instruction, based on their experiences with a particular se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
(100 reference statements)
0
15
1
Order By: Relevance
“…Last but not least, in contrast to our previous research in medium-sized classrooms, one of the explanations (in addition to the complexities to arrange sub-group meetings in a large lecture room) why team divisions in this setting were not the primary predictor for learning at the end of the module may have been the lack of constructive alignment (Biggs & Tang, 2007;Struyven et al, 2011). The aims of team work (i.e.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Last but not least, in contrast to our previous research in medium-sized classrooms, one of the explanations (in addition to the complexities to arrange sub-group meetings in a large lecture room) why team divisions in this setting were not the primary predictor for learning at the end of the module may have been the lack of constructive alignment (Biggs & Tang, 2007;Struyven et al, 2011). The aims of team work (i.e.…”
Section: Discussioncontrasting
confidence: 40%
“…However, in the last 20 years, the use of team-learning in higher education to engage students in active learning has increased (Decuyper, Dochy, & Van den Bossche, 2010), even when teaching in large classrooms (Struyven, Dochy, & Janssens, 2011).…”
mentioning
confidence: 99%
“…It is believed that academics who have a more student-centred approach to teaching are more likely to achieve conceptual change amongst students, while academics who have a more teacher-centred approach to teaching are more likely to aim at the transmission of information and knowledge to students (Norton, Richardson, Hartley, Newstead, & Mayes, 2005;Postareff, et al, 2007;Prosser & Trigwell, 1999;Struyven, Dochy, & Janssens, 2011). Previous research in higher education has found that teachers adopting a more student-focussed approach to teaching are more likely to stimulate students to adopt a deep rather than a surface approach to their learning (Gow & Kember, 1993;Prosser & Trigwell, 1999).…”
Section: Teachers Beliefs and Intentions Towards Learning Facilitatiomentioning
confidence: 99%
“…Measuring the effectiveness of different didactic methods is not an easy task. Research on this topic suggests that the effectiveness of active learning methods compared to traditional lectures depends on a range of factors, including contextual factors and student characteristics (Struyven et al, 2011). In other words, the effectiveness of active learning tools like games and role plays cannot be measured as a function of the properties of the tools alone.…”
Section: Experiences With the Role Playmentioning
confidence: 99%